Effect of ceramic barriers of different thicknesses on microhardness of light-cured resin cements - do Nascimento, Yasmin Alves; Correia, Ayla Macyelle de Oliveira [UNESP]; Lima, Darlon Martins; Griza, Sandro; Takeshita, Wilton Mitsunari; de Mendonça, Adriano Augusto Melo (Quintessence Publishing, 2017)
This study evaluated the microhardness of two resin cements and a low-viscosity resin composite when light-cured under different ceramic thicknesses. A total of 20 samples (10.0 × 1.0 mm) of each material were polymerized by means of a LED light source with an intensity of 1,100 mW/cm2 for 20 seconds. For each experimental group, different ceramic thicknesses (0.5 mm, 1.0 mm, and 1.5 mm) were applied to each sample. For the control group, the samples were polymerized without the presence of ceramics. Each material was then stored in dry vials that inhibited the passage of light for a period of 24 hours. After that time, each sample underwent Vickers hardness test (HMV, Shimadzu: 25 g/10 seconds). The data were collected and analyzed using analysis of variance and Tukey test (P < .05). For the control group, RelyX Veneer (3m ESPE), Filtek Flow Z350XT (3M ESPE), and Allcem Veneer (FGM) showed mean microhardness values and standard deviations of 44.42 ± 4.9, 44.25 ± 2.4, and 31.71 ± 2.4, respectively. The lowest microhardness value (24.13) was found when the greatest ceramic thickness (1.5 mm) was used on the Allcem Veneer cement (P < .01). The microhardness of resin-based materials was affected when the 1.5-mm-thick ceramic material was interposed during photoactivation.